Answer:
3( n +
)² -
= 0
Step-by-step explanation:
3n² = 6 - 17n ⇔ 3n² + 17n - 6 = 0
3( n² + 2 ×
n + (
)² - (
)² - 2 ) = 0
3( n +
)² - 3 ×
- 6 = 0
3( n +
)² -
= 0
Answer:
The jeweler made 9 necklaces.
The jeweler made 8 bracelets.
Step-by-step explanation:
x = number of bracelets
y = number of necklaces
17 = x + y
238 = 5x + 22y
Make one of the coefficients, x, the same.
17 = x + y
Multiply this equation by 5.
85 = 5x + 5y
Subtract the equations to get rid of x.
(238 = 5x + 22y) - (85 = 5x + 5y)
(5x - 5x) + (22y - 5y) = 238 - 85
22y - 5y = 238 - 85
17y = 153
y = 153/17 = 9
The jeweler made 9 necklaces. Substitute this back into one of the equations to find x.
17 = x + y
17 = x + 9
17 - 9 = x
x = 8
238 = 5x + 22y
238 = 5x + 22(9)
238 = 5x + 198
238 - 198 = 5x
40 = 5x
x = 40/5
x = 8
The jeweler made 8 bracelets.
Answer:
I and III
Step-by-step explanation:
mark me as brainliest
Answer:
7
Step-by-step explanation:
Put the m value where m is
9/3+4
9/3 simplified is 3
3+4=7
Answer:
15 because 3 x 5 equals 15
Step-by-step explanation: